"Monuments of Folly": Frederick Douglass, Charlottesville, and the National Religions of America. (17th August 2020) - Lê, David
Abstract: Heather Heyer's murder at a 2017 white supremacist rally in Charlottesville, which was organized to defend a monument to Robert E. Lee, offers an occasion to reflect on Robert Bellah's notion of "American civil religion." Here I seek to reconstruct that concept in terms of "American national religion" to train scholarly attention on the privileged roles of nation and race in organizing the religion of Americans, as Americans. By looking at the material forms of this religion through the lens of Frederick Douglass's writings about American national memorialization, I argue that we can better assess the actual as opposed to the ideal content of this religion. We can, further, avoid the Pollyannaish race-blindness endemic to the scholarly discourse on American civil religion. My reconstruction foregrounds a model of "hegemonic articulation" in which violence, power, and exclusion are taken to be the rule, rather than the exception, in defining America's national religion.